Local Government Policies Related To Transfer Of Agricultural Land Functions To Non Agricultural Governments - Sutapa Mulya Sanjaya; Widayati Widayati (UNISSULA Semarang, 2021)
The purpose of this study was to determine and analyze the Batang Regency Government's Policy Regarding the Transfer of Agricultural Land Functions to Non-Agriculture.In this paper, the author uses a sociological juridical method. In the discussion that the uncontrolled transfer of agricultural land to non-agricultural functions can have an impact in the form of disturbances to the balance of the environment and a decrease in agricultural production, especially rice. Disturbances to the environment occur, for example, housing construction causes flooding in the area below. In general, the Batang Regency Government's policies related to the conversion of agricultural land to non-agriculture in the form of several regulations and their implementation have not fully protected food agricultural land as mandated by the Law on Protection of Sustainable Food Agricultural Land. The stipulation of the Regional Regulation on the Batang Regency Spatial Planning has not been followed by the stipulation of detailed regulations.